Hubungan Pendidikan Kesehatan dengan Kejadian Hiperbilirubinemia di Rumah Sakit - Deswita (NERS Jurnal Keperawatan, 2014)
The purpose of the research was describing the effect of health education at knowledge and attitude of the mother, and incidence of hyperbilirubinemia at the newborn. The research was quasi experimental with pretest posttest design. The samples were 30 post-partum and divided into two group, control and intervention group. Samples selected with non-probability sampling-consecutive sampling. The result showed that postpartum knowledge and attitude was increased after intervention. Incidence of hyperbilirubinemia in intervention group is higher than control group (p=0,651). The research recommended that health education should be given since antenatal period.